Taping for achilles tendinitis on the ATP tennis circuit - Tintschl, M.; Bastholt, P. (2002)
Achilles tendinitis is not uncommon among professional tennis players. This article describes the technique used for taping when there is tendinitis of the Achilles tendon. Taping helps protect the Achilles by limiting stretching of the tendon. In mild cases, this may allow the athlete to resume or continue sports activity.